TAZKIYÄ€T AL-NAFS MELALUI PENDEKATAN TASAWUF DAN FIKIH DALAM MEMBANGUN KESALEHAN SOSIAL DAN RELEGIOSITAS MASYARAKAT - Khotib Khotib; Muhammad Ufuqul Mubin (IBDA` : Jurnal Kajian Islam dan Budaya, 2019)
This research aims to find the concept of Tazkiyat al-Nafs in the perspective of Sufism in the Jamiyyah Qodiriyah wa Naqsabandiyah (TQN) Rejoso Peterongan Jombang and the perspective of fiqh at the Islamic Boarding School Sunan Drajad Paciran Lamongan, to find construct of thought of social piety and the religiosity of community through the concept of Tazkiyat al-Nafs in building social piety and the religiosity of community. Using the field research approach with factual historical models and analysis contests (Unitizing, Sampling, Recording, Reducing, Inferring, Narrating), it is expected that the results of this study is able to find the concept of Tazkiyat al-Nafs from various perspectives. The results of this research interpret Tazkiyat al-Nafs as a process of developing human beings to have pure creed, wide knowledge, sacred soul, and life worthy of worship, developing human beings to have pure souls and noble with fellow human beings, developing human beings with healthy souls and free from despicable behavior endanger the soul by means of rituals of worship, surrender to the Murshid and learn the praiseworthy behavior of the scholars. Penelitian ini juga bertujuan untuk menemukan konsep Tazkiyat al-Nafs perspektif tasawuf di Jamiyyah Tarekat Qodiriyah wa Naqsabandiyah (TQN) Rejoso Peterongan Jombang dan perspektif fikih di Pondok Pesantren Sunan Drajad Paciran Lamongan, menemukan konstruksi pemikiran tentang kesalehan sosial dan religiositas masyarakat melalui konsep Tazkiyat al-Nafs dalam membangun kesalehan sosial dan religiositas masyarakat. Dengan pendekatan field research dengan model historis faktual serta contens analysis (Unitizing, Sampling, Recording, Reducing, Inferring, Narrating) diharapkan hasil penelitian ini bisa menemukan konsep Tazkiyat al-Nafs dari berbagai perspektif. Hasil riset ini memaknai Tazkiyat al-Nafs sebagai proses pembentukan manusia yang suci akidahnya, luas ilmunya, suci jiwanya, dan kehidupannya bernilai Ibadah, membentuk manusia yang suci jiwanya dan berakhlak mulia dengan sesama manusia, membentuk manusia dengan jiwa sehat dan terbebas dari perilaku tercela yang mebahayakan jiwa dengan cara ritualritual ibadah, penyerahan diri kepada Mursyid dan belajar perilaku terpuji dari para ulama.